HSP90 inhibitors promote cell death by degrading Met and BCR::ABL1 in both imatinib-resistant and -sensitive chronic myeloid leukemia cells - Masanobu Tsubaki; Taira Matsuo; Rie Komori; Noriaki Nagai; Tetsushi Yamamoto; Shozo Nishida (Future Journal of Pharmaceutical Sciences)
Abstract Background Chronic myeloid leukemia is associated with a more favorable prognosis following treatment with BCR::ABL1 tyrosine kinase inhibitors (TKIs). Nonetheless, about 40% of affected individuals with CML display resistance or intolerance towards BCR::ABL1 TKIs. Heat shock protein 90 (HSP90) functions as a molecular chaperone and is known for its overexpression in various types of cancer, thereby HSP90 is a potential candidate for the treatment of BCR::ABL1 TKI-resistant and -sensitive CML. In present study, we aimed to investigate whether HSP90 inhibitors promote cell death in imatinib-resistant and -sensitive CML cells. Results KW-2478 and NVP-AUY922, which are HSP90 inhibitors, promoted cell death in both imatinib-resistant and -sensitive CML cells. Imatinib-resistant cells showed greater sensitivity to HSP90 inhibitors in comparison to imatinib-sensitive cells. KW-2478 inhibited the activation of Akt, extracellular regulated protein kinase 1/2, and c-Jun N-terminal kinase 1/2 in imatinib-resistant and -sensitive CML cells by promoting Met and BCR::ABL1 degradation. Conclusion These findings indicate inhibition of HSP90 such as KW-2478 and NVP-AUY922 as potential candidates for CML therapy.